E-Transaction in Digital Era - T Rohmawati; H Zulkipli (Fakultas Ekonomi, Universitas Negeri Jakarta, 2021)
The purpose of this study is to analyze the habits of students in the information technology in conducting transactions either in cash or by using e-money. Questionnaire was a method used in this study by distributing selected questionnaires only to students. Analysis of the results showed that the students preferred to use e-money for transactions because it was more effective and more efficient than paying in cash. It could be also because it was influenced by their shopping habits through social media and the globalization era. On the other hand, they needed cash and relatively bigger wallet for cash payments. Consequently, e- money was preferred by students compared to cash payments.